Implementasi Strategi Guru Dalam Meningkatkan Kompetensi Sikap Sosial Siswa Masa Pandemi Covid 19 Di Madrasah Aliyah Negeri Wonogiri Tahun Pelajaran 2020/2021 - Fitriyani, Siti Ida (Universitas Yudharta Pasuruan, 2022)
The problem faced today is that the teaching and learning process in schools only focuses on the knowledge aspect. While the affective aspects and psychomotor aspects are less attention. In the learning process, educators focus on how to only explain, not so that they pay less attention to how students' soft skills are. While the soft skills in question are the attitudinal competencies possessed by students during and outside learning. This study aims to determine 1) the implementation of teachers in improving the competence of students' social attitudes. 2) To determine the supporting and inhibiting factors in the implementation of teachers in improving the competence of social attitudes in students. This research was conducted in 2021. This research is a field research with a qualitative descriptive approach. The results showed that: the strategy of inculcating students' social attitudes was carried out in learning activities that were carried out repeatedly and continuously so that they could indirectly instill social attitudes into students. The habits applied in this madrasa are as follows: 1) planning by the teacher in the form of preparing lesson plans, choosing active learning methods, preparing learning materials, inviting students to express opinions, inviting students to remind each other in doing assignments, reminding to speak politely, reminding to do assignments on time, giving penalties to students who come late, getting children to do 3S (smiles, greetings, greetings) when meeting with teachers, giving reprimands to students who often don't do assignments and don't take lessons. 2) The factors for inculcating students' social attitudes are supporting and inhibiting factors. Supporting factors include Awareness, Student Willingness, Teacher Responsibilities, a conducive environment, students' daily interactions. While the inhibiting factors include different student backgrounds, the community environment. Limitations in inculcating social attitudes.